Mechanical characterization of composite solid rocket propellant based on hydroxy-terminated polybutadiene - Gligorijević Nikola I.; Rodić Vesna Ž.; Živković Saša Ž.; Pavković Bojan M.; Nikolić Momčilo M.; Kozomara Stevan M.; Subotić Sredoje D. (Hemijska Industrija, 2016)
This paper presents the procedure of uniaxial mechanical characterization of composite solid rocket propellant based on hydroxy-terminated polybutadiene (HTPB), whose mechanical properties strongly depend on temperature, strain rate, natural aging and accumulated damage. A method of processing data is presented in order to determine time-temperature shift factor and master curves for tensile strength, ultimate strain and relaxation modulus, depending on reduced time. Functional dependences of these features represent an input for structural analysis of a rocket motor propellant grain. The effects of natural aging on the mechanical properties are also considered. [Projekat Ministarstva nauke Republike Srbije, br. TR 36050: Research and development of unmanned aircraft in support of traffic infrastructure monitoring]